Highly efficient blue and warm white organic light-emitting diodes with a simplified structure. (18th February 2016) - Li, Xiang-Long; Ouyang, Xinhua; Chen, Dongcheng; Cai, Xinyi; Liu, Ming; Ge, Ziyi; Cao, Yong; Su, Shi-Jian
Abstract: Two blue fluorescent emitters were utilized to construct simplified organic light-emitting diodes (OLEDs) and the remarkable difference in device performance was carefully illustrated. A maximum current efficiency of 4.84 cd A −1 (corresponding to a quantum efficiency of 4.29%) with a Commission Internationale de l'Eclairage (CIE) coordinate of (0.144, 0.127) was achieved by using N, N-diphenyl-4″-(1-phenyl-1H-benzo[d]imidazol-2-yl)-[1, 1′:4′, 1″-terphenyl]-4-amine (BBPI) as a non-doped emission layer of the simplified blue OLEDs without carrier-transport layers. In addition, simplified fluorescent/phosphorescent (F/P) hybrid warm white OLEDs without carrier-transport layers were fabricated by utilizing BBPI as (1) the blue emitter and (2) the host of a complementary yellow phosphorescent emitter (PO-01). A maximum current efficiency of 36.8 cd A −1 and a maximum power efficiency of 38.6 lm W −1 were achieved as a result of efficient energy transfer from the host to the guest and good triplet exciton confinement on the phosphorescent molecules. The blue and white OLEDs are among the most efficient simplified fluorescent blue and F/P hybrid white devices, and their performance is even comparable to that of most previously reported complicated multi-layer devices with carrier-transport layers.